CT dimensions, volumes and densities of normal canine eyes. (11th April 2015) - Salgüero, R.; Johnson, V.; Williams, D.; Hartley, C.; Holmes, M.; Dennis, R.; Herrtage, M.
Abstract : Although ultrasound and MRI are the imaging modalities of choice for the investigation of ocular diseases, the eyes are included in routine CT examinations of the head and should be examined as part of the complete evaluation. This report describes the dimensions, volumes and densities of the normal canine globe in CT. Forty‐four eyes were studied. The mean axial length of the globe was 2.09 cm and its mean volume was 4.65 cm 3 . The mean anteroposterior distance of the anterior chamber was 0.4 cm and of the vitreous chamber was 0.96 cm. There was a statistically significant difference between the mean aqueous humour density, 14.76 Hounsfield units (HU), and the mean vitreous humour density, 11.20 HU (P=0.0009). Statistically significant differences were also seen in both humours in precontrast and postcontrast studies. The mean anteroposterior dimension of the lens was 0.74 cm; its mean equatorial distance was 1.15 cm. The mean volume was 0.43 cm 3 and its mean density was 131.9 HU. There was contrast enhancement of the ciliary body, iris and retina/sclera/choroid complex. This study provides reference values to help in the interpretation of ocular structures on CT scans of the head, where incidental findings can change the medical management of specific cases.